Transformation of Malignant Melanoma From Giant Nevus in Infantile Penis - Lee, Dong Hwan; Kim, Min Ji; Lee, Il Jae; Park, Dong Ha (Frontiers in Surgery, 2020)
Background Malignant melanoma is the most serious type of skin cancer, and its incidence increases with age. Malignant melanoma in infants has been rarely reported in the literature. Herein, we report a case of malignant transformation of a nodular lesion found in the penis of a patient with a giant congenital nevus. Case presentation: A 1-month-old male patient was admitted due to the presence of a giant congenital nevus involving the lower abdomen, bilateral inguinal areas, genitals, and left thigh and knee. Six months later, nodules measuring 1 cm in diameter protruding from the genital area were noted, and a part of the nodule was removed via elliptical excision with the patient under general anesthesia. Gross examination showed an edematous lesion similar to a neurofibroma and with unclear boundaries. Biopsy revealed a malignant melanoma, with the Breslow thickness of at least 3 mm, and absence of lymphovascular invasion; the biopsy confirmed incomplete excision. The patient was scheduled for radical resection, but reconstruction was not performed following surgical resection due to the guardian’s refusal. Hence, the patient only received an adjuvant medical treatment and eventually died. Conclusion We reported a rare case of an infant with a malignant melanoma in the penis. Congenital malignant melanoma rarely occurs in infants; however, due to its fatal consequences, follow-up should be performed to assess for malignant changes.